Knowledge, attitude and practice of shared decision-making among Indian physiotherapists - Parthasarathi, Brinda; Francis, Saritha K.; P. H., Sandeep; Raja, Kavitha (International Journal Of Community Medicine And Public Health, 2025)
Background: Shared decision-making (SDM) is a collaborative approach in which physiotherapists and patients jointly make treatment decisions by integrating clinical evidence with patient preferences. Shared decision making has been associated with improved rehabilitation outcomes globally yet its uptake in low- and middle-income countries like India remains unclear. Hence, the objective of this study was to assess the knowledge, attitude, and practice of shared decision-making among Indian physiotherapists. Methods: Study incorporated a cross-sectional survey among 109 physiotherapists across India using a validated questionnaire assessing knowledge, attitudes of shared decision-making implementation across various clinical conditions, and real-world shared decision-making practices. Data were collected and analysed using descriptive statistics. Results: While 99% of participants correctly identified the purpose of shared decision making only 3.66% demonstrated full knowledge, revealing a significant deficit. While attitudes were most favourable in chronic and orthopedic care, half viewed shared decision making as confusing or time consuming. Although many discussed conditions and treatment options with patients, 66% did not communicate evidence-based benefits and risks highlighting lack of evidence practice in patient-centred care. Conclusions: The study revealed limited comprehensive knowledge but a generally positive attitude and partial adoption of shared decision-making practices among Indian physiotherapists. These findings highlight a need for targeted education and training to enhance evidence-based shared decision-making in physiotherapy practice.